Burden of influenza‐associated outpatient influenza‐like illness consultations in China, 2006‐2015: A population‐based study - Feng, Luzhao (Influenza Other Respir Viruses, 2019)
BACKGROUND: Human influenza virus infections cause a considerable burden of morbidity and mortality worldwide each year. Understanding regional influenza‐associated outpatient burden is crucial for formulating control strategies against influenza viruses. METHODS: We extracted the national sentinel surveillance data on outpatient visits due to influenza‐like‐illness (ILI) and virological confirmation of sentinel specimens from 30 provinces of China from 2006 to 2015. Generalized additive regression models were fitted to estimate influenza‐associated excess ILI outpatient burden for each individual province, accounting for seasonal baselines and meteorological factors. RESULTS: Influenza was associated with an average of 2.5 excess ILI consultations per 1000 person‐years (py) in 30 provinces of China each year from 2006 to 2015. Influenza A(H1N1)pdm09 led to a higher number of influenza‐associated ILI consultations in 2009 across all provinces compared with other years. The excess ILI burden was 4.5 per 1000 py among children aged below 15 years old, substantially higher than that in adults. CONCLUSIONS: Human influenza viruses caused considerable impact on population morbidity, with a consequent healthcare and economic burden. This study provided the evidence for planning of vaccination programs in China and a framework to estimate burden of influenza‐associated outpatient consultations.